Anatomical Variations of the Biceps Brachii and their Effect on Supination and Flexion Torque. A Cross-Sectional Study - Aisha Hassan Brohi, Afifa Waseem, Amna Mughal, Farhana Jafri, Waqas Qurshi, Nimrah Fahim (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The biceps brachii is a major muscle involved in elbow flexion and forearm supination. While classically composed of two heads, it demonstrates notable anatomical variations such as accessory heads, proximal tendon bifurcation, and altered muscle belly length. These variations may influence torque generation, but their in vivo functional impact has been insufficiently studied. Objective: To determine the prevalence of anatomical variations of the biceps brachii and assess their effect on elbow flexion and forearm supination torque. Methods: A descriptive analytical cross-sectional study was conducted from January to May 2023 in the Department of Anatomy, Dow Medical College, Dow University of Health Sciences, Karachi, and the Department of Anatomy, Fatima Jinnah Medical University, Lahore, Pakistan. Ninety healthy adults (45 males, 45 females; aged 18–55 years) underwent bilateral ultrasonographic assessment to document number of heads, tendon morphology, and muscle belly length. Elbow flexion and forearm supination torque were measured at 60°/s using a Biodex System 4 dynamometer. Statistical analysis was performed in SPSS v26, with significance set at p<0.05. Results: Anatomical variations were identified in 27 participants (30.0%), most frequently accessory heads (14.4%), followed by proximal tendon bifurcation (8.9%) and short muscle belly (6.7%). Accessory heads were associated with significantly higher flexion torque (67.8 ± 7.1 Nm) compared to normal anatomy (62.9 ± 6.5 Nm; p=0.018). Short muscle bellies produced significantly lower supination torque (45.1 ± 5.4 Nm) compared to normal (48.4 ± 5.1 Nm; p=0.042). Muscle belly length correlated positively with supination torque (r=0.39, p=0.001). Conclusion: Biceps brachii variations are common and can influence performance. Accessory heads enhance flexion strength, whereas short muscle bellies reduce supination capacity. Recognition of these variations is important in clinical, surgical, and rehabilitative contexts. Keywords: Biceps brachii, anatomical variation, elbow flexion, supination torque, muscle belly length, biomechanics.